PERAN KOMITMEN PROFESIONAL AUDITOR DALAM HUBUNGAN ANTARA KONFLIK PEKERJAAN KELUARGA DENGAN KEINGINAN BERPINDAH (Studi Empiris pada Auditor Kantor Akuntan Publik di Jawa Tengah) - Eko Madyo Sutanto; Sugiarti . (Universitas Sahid Surakarta, 2017)
The purpose of this study is to examine the inï¬‚uence of work-family conï¬‚ict on turnover intentions with professional commitment as an intervening variable. Work-family conï¬‚ict has two dimensions, i.e. work interfering with family (WIF) and family interfering with work (FIW). Turnover intentions may arise because of professional ommitment and work-family conï¬‚ict. This study used a questionnaire survey for data collection. The sampling technique used was non-probability sampling with purposive sampling method. Data were collected by a mail-survey on 82 auditors in Indonesian audit frms. Data were analyzed by Structural Equation Model (SEM) with Smart PLS (Partial Least Square) program.The results of this study found that there was no signifcant relationship between work interfering with family (WIF) and turnover intentions auditor,and there is no signifcant relationship between family interfering with work (FIW) and turnover intentions auditor, there is signifkcant relationship between the work interfering with family (WIF) and professional commitment, there is signifkcant relationship between the family interfering with work (FIW) and professional commitment. There is signifcant relationship professional commitment and turnover intentions auditors.